Extensive testing of a multi-locus sequence typing scheme for Giardia duodenalis assemblage A confirms its good discriminatory power - Klotz, Christian; Sannella, Anna Rosa; Weisz, Filip; Chaudhry, Umer; Sroka, Jacek; Tůmová, Pavla; Nohýnková, Eva; Ignatius, Ralf; Aebischer, Toni; Betson, Martha; Troell, Karin; Cacciò, Simone M. (Parasites & vectors, 2022)
The flagellated parasite Giardia duodenalis is a major and global cause of diarrhoeal disease. Eight genetically very distinct groups, known as assemblages A to H, have been recognized in the G. duodenalis species complex, two of which (assemblages A and B) infect humans and other mammalian hosts. Informative typing schemes are essential to understand transmission pathways, characterize outbreaks and trace zoonotic transmission. In this study, we evaluated a published multi-locus sequence typing (MLST) scheme for G. duodenalis assemblage A, which is based on six polymorphic markers. We genotyped 60 human-derived and 11 animal-derived G. duodenalis isolates collected in Europe and on other continents based on the published protocol. After retrieving previously published genotyping data and excluding isolates whose sequences showed allelic sequence heterozygosity, we analysed a dataset comprising 146 isolates. We identified novel variants at five of the six markers and identified 78 distinct MLST types in the overall dataset. Phylogenetic interpretation of typing data confirmed that sub-assemblage AII only comprises human-derived isolates, whereas sub-assemblage AI comprises all animal-derived isolates and a few human-derived isolates, suggesting limited zoonotic transmission. Within sub-assemblage AII, isolates from two outbreaks, which occurred in Sweden and Italy, respectively, had unique and distinct MLST types. Population genetic analysis showed a lack of clustering by geographical origin of the isolates. The MLST scheme evaluated provides sufficient discriminatory power for epidemiological studies of G. duodenalis assemblage A.